Hip rotation obtained via conventional and functional knee joint axis calibration in the context of femoral derotation osteotomy - Musagara, Arik Rehani; Götze, Marco; Wolf, Sebastian I. (Gait & posture, 2023)
Transversally measured hip rotation can add valuable information in the indication of femoral derotation osteotomy (FDO) (Dreher 2007), which serves as the gold standard in the treatment of internally rotated gait. Typically, studies on gait analyses in the context of FDO relied on the conventional calibration of the knee joint axis (KJA) based on palpation of the epicondyles. However, researchers regularly face discrepancies between planned FDO angle, pre-post changes in anteversion and pre-post changes in hip rotation (Böhm 2015, Putz 2016). Apart from previously discussed factors, we hypothesized that a functional calibration of the KJA might lead to smaller differences between aforementioned parameters and therefore provide more coherent results than the conventional method. Does a functional KJA calibration allow for smaller differences between intraoperative FDO angle and pre-post changes in mean hip rotation in stance (mHipRotSt)? 14 patients (mean age at surgery: 16.2 ± 9.5 years) scheduled for FDO were examined retrospectively in this study. 3D gait analysis including functional KJA calibration and rotational MRIs (available in 8 of 14 patients) for estimating anteversion were measured pre- (1 day) and post-FDO (11.7 ± 3.1 months). Functional calibration included three unassisted, unloaded knee flexion-extension movements in single limb stance and were repeated for both legs. Subsequently the SARA algorithm (Ehrig 2007) was applied. Conventional estimation of the KJA was done with the Knee Alignment Device method. FDO angle was documented during surgery and was measured intraoperatively with a goniometer. Postoperative mHipRotSt was significantly smaller (p <0.001) for both conventional and functional method than before surgery (Table 1). A significant, high correlation was observed between the pre-post FDO change of conventionally measured mHipRotSt and intraoperative external FDO angle (r = 0.62, p < 0.01). For the functionally measured change in mHipRotSt a non-significant, moderate correlation (r = 0.41, p = 0.1) was found. Discrepancies between change in mHipRotSt and mean FDO angle/ change in anteversion were 3.4°/ 1.6° conventionally and 10.4°/ 8.4° functionally measured. Correlation analysis between preoperative Range of motion (ROM) during calibration movement and the change in mHipRotSt revealed a weak, non-significant correlation (r = 0.16, p = 0.549). [Display omitted] The conventional method is more in alignment with the aimed intraoperative FDO and therefore appears as the preferable option in the decision-making process in the context of FDO. Also changes in the anteversion were closer to conventionally measured values. Analysis on the presumably more restricted ROM did not indicate that it had a strong influence on the differences between pre- and postoperative mHipRotSt.